THREE ELEMENTS STRUCTURE AND SOUND EXPECTATION CONCEPT IN SOUNDSCAPE – A CASE STUDY OF THE NEW LAKESIDE PARK, HANG ZHOU - Ge Jiang; Guo Min; Hu Jun; Yue Miao (International Association of Lowland Technology, 2012)
The three elements structure